Effects of Macrophage Inflammatory Protein 1 Alpha and Beta Chemokine Concentrations in the Progression of Endometriosis - Marcin Sadłocha; Jakub Toczek; Zenon Czuba; Rafał Stojko (Clinical and Experimental Obstetrics & Gynecology)
Objective: The aim of this study was to understand the pathophysiologic mechanisms of macrophage inflammatory protein 1 alpha (MIP1a) and beta (MIP1b) chemokines in endometriosis, and to understand the immuno-pathophysiology underlying the progression of this disease. Methods: Analyses and conclusions outlined in this study were based on in vitro experiments conducted using supernatants collected from cultured lymphocytes taken from women with endometriosis and from healthy donors. The study group included 30 patients meeting the outlined inclusion criteria who were diagnosed at various clinical stages of endometriosis following a laparoscopic procedure and subsequent histopathological examination. The control group were 50 patients with infertility but without endometriosis. Blood samples were taken and the resulting buffy coat was used to establish lymphocyte cultures. After plating the cells, phytohaemagglutinin (PHA) was added and after 24 hours of incubation, supernatants were collected by centrifugation and subjected to analysis. Results: MIP1a and MIP1b levels in PHA-stimulated lymphocyte cultures from women with endometriosis were elevated when compared to controls, and this difference was highly statistically significant for both cytokines (p = 0.00001 and p = 0.000026, respectively). Additionally, we analyzed the correlation between the occurrence of endometriosis and PHA-stimulated chemokine concentration in lymphocyte culture supernatants. Both MIP1a and MIP1b exhibited a statistical significance with the presence of endometriosis (p = 0.00001). Conclusions: In this study, we observed a significant increase in secretion of selected chemokine factors in in vitro cultures of lymphocytes from women diagnosed with endometriosis. This feature may indicate an essential role for these chemotactic factors in the pathogenesis of endometriosis. To fully understand the influence of MIP1a and MIP1b on disease progression, it will be necessary in future studies to determine chemokine concentrations at each stage of endometriosis.